A Compact Planar Low-Pass Filter Based on SRR-Metamateria - Badr Nasiri; Ahmed Errkik; Jamal Zbitou; Abdelali Tajmouati; Larbi El Abdellaoui; Mohamed Latrach (Institute of Advanced Engineering and Science, 2018)
In this work, a novel design of a Microstrip Low-pass filter based on metamaterial square split ring resonators (SRRs) is proposed. The SRRs has been added to obtain a reduced size and high performances. The filter is designed on an FR-4 substrate having a thickness of 1.6mm, a dielectric constant of 4.4 and loss tangent of 0.025. The proposed low-pass filter is characterized by a cutoff frequency of 2.4 GHz and an attenuation level below than -20dB in the stopband. The LPF is designed, simulated and optimized by using two electromagnetic solvers CST microwave studio and ADS. The computed results obtained by both solvers are in good agreement. The total surface area of the proposed circuit is 18x18mm2 excluding the feed line, its size is miniaturized by 40% compared to the conventional filter. The experimental results illustrate that the filter achieves very good electrical performances in the passband with a low insertion loss of 0.2 dB. Moreover, a suppression level can reach more than 35 dB in the rejected band.